Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/pmic.201100107
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative temporal proteomic analysis of human embryonic stem cell differentiation into oligodendrocyte progenitor cells

Abstract: Oligodendrocytes (OLs) are glial cells of the central nervous system which produce myelin. Cultured OLs provide immense therapeutic opportunities for treating a variety of neurological conditions. One of the most promising sources for such therapies is human embryonic stem cells (ESCs), as well as providing a model to study human oligodendrocyte development. For these purposes, an investigation of proteome level changes is critical for understanding the process of OL differentiation. In this report, an iTRAQ-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 51 publications
(55 reference statements)
1
37
0
Order By: Relevance
“…Data processing for protein identification and quantification of ICPL- labeled proteins was performed using Proteome Discoverer version 1.3.0.339 (Thermo Scientific) as described before [23], [27][29]. Briefly, Proteome Discoverer software performed automated statistical analysis of the results and used unique peptides to calculate accurate relative protein quantification.…”
Section: Methodsmentioning
confidence: 99%
“…Data processing for protein identification and quantification of ICPL- labeled proteins was performed using Proteome Discoverer version 1.3.0.339 (Thermo Scientific) as described before [23], [27][29]. Briefly, Proteome Discoverer software performed automated statistical analysis of the results and used unique peptides to calculate accurate relative protein quantification.…”
Section: Methodsmentioning
confidence: 99%
“…Following up on the role of HMGA2 in regulating p16 Ink4a expression and NSC proliferation, additional studies have reported that the HMGA family of proteins maintain NSC/NPC chromatin in the open state during early development [19]. Moreover, HMGA proteins were identified by iTRAQ proteomic analysis as being expressed during oligodendrocyte precursor cell (OPC) differentiation [20], and transcriptional profiling studies have found that NSCs express HMGB1, HMGB2 and HMGB3 mRNA [21]. A recent study in zebrafish reported that HMGB1 is critical for early brain development, since morpholino-knockdown of HMGB1 expression created forebrain defects and ablation of the catecholamine network [22].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Letzen et al, showed miRNA profiles during different stages of oligodendrocyte differentiation from hESCs, which possibly presents key markers of oligodendrocyte maturation in vivo [109]. Further, Chaerkady et al, demonstrated several novel proteins, such as fatty acid-binding protein and thrombospondin-1, which are probably involved in oligodendrocyte differentiation and maturation, by presenting an extensive proteomic profiling of oligodendrocytes derived from hESCs [110]. It is through these studies that a comprehensive understanding of molecular and cellular regulators of oligodendrocyte development will be achieved, providing investigators with the most powerful selection criteria for transplantation studies.…”
Section: Applications Of Oligodendrocytes Derived From Hescsmentioning
confidence: 99%